Pemanfaatan Kulit Labu Kuning dan Kulit Pisang Raja Pada Pembuatan Bioetanol Konteks Teknologi Ramah Lingkungan - Pathonawiratama, Gustin; Nursaadah, Euis; Wardana, Rendy Wikrama; Sutarno, Sutarno; Johan, Henny (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to evaluate the potential of yellow pumpkin peel (Cucurbita moschata) and king banana peel (Musa paradisiaca) as raw materials for bioethanol production, based on the alcohol content produced. The bioethanol production process includes hydrolysis using 5% HCl, fermentation for 7 days with adding nutrients (NPK and urea), and purification through distillation. The research results show that the combination of yellow pumpkin peel and king banana peel, adding NPK, produces the highest ethanol content of 13%. Meanwhile, the lowest content of 4% was obtained from the fermentation of the king banana peel without additional nutrients. The addition of nutrients, particularly NPK, has been proven to enhance the activity of microorganisms in natural fermentation, thereby accelerating the conversion of carbohydrates into ethanol. With the ethanol content produced, the bioethanol from this organic waste can be used practically as E5-type blended fuel without requiring any modifications to vehicle engines. This result shows that fruit peel waste can be an environmentally friendly and economical alternative for renewable energy.